Penentuan Kadar NPK (Nitrogen, Fosfor dan Kalium) dari Pelepah Aren (Arenga Pinnata M.) - Hesti; Rahmanpiu; La Rudi (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2023)
Research has been carried out to determine the levels of NPK (Nitrogen, Phosphorus and Potassium) in the palm fronds (Arenga pinnata M.). Palm fronds can be used as a growing medium. One indicator of a material that can be used as a growing medium is the availability of nutrients. So the purpose of this study was to determine the feasibility of the palm midrib (Arenga pinnata M.) to be used as a growing medium. The method used to determine the levels of NPK (Nitrogen, Phosphorus and Potassium) used a different method. Determination of nitrogen content was determined using the Kjeldahl method, phosphorus using the UV-Vis Spectrophotometer method and potassium using the Atomic Absorption Spectrophotometer method. Based on the results of research conducted, on the palm fronds, the results obtained with nitrogen levels of 0.171%, Phosphorus of 1.826% and Potassium of 0.0022%. From the results of these studies that meet the requirements as a planting medium is Phosphorus so that the palm fronds can be recommended to be used as a planting medium.